A further experience of propranolol for severe infantile hemangiomas of the face: an observational study. Issue 4 (18th February 2014) - Greco, Antonella; D'Erme, Angelo Massimiliano; Zamma Gallarati, Barbara; Caputo, Roberto; de Martino, Maurizio
Abstract Infantile hemangiomas (IHs) are the most common proliferating embrional tumors of infancy, which are constituted by endothelial cell hyperproliferation. The authors want to report their observations of further 14 patients suffering from complicated IHs involving the facial district who were treated with propranolol. 14 patients, with ages between 3 and 12 months, completed a cycle of treatment with propanolol. The observational study aimed at focusing IHs involving the facial district. The treatment with propranolol showed good to very good results in the major part of the treated young patients. The authors want to report their experience and add more data in the confirmation of the use of β‐blockers for IH (either in efficacy or in safety profile), focusing on the efficacy of propanolol when IHs involve the face.